GERMINATION AND INITIAL GROWTH IN CORIANDER SUBSTRATE IRRIGATED WITH SALINE WATER - Sales, M. A. L.; Moreira, F. J. C.; Eloi, W. M.; Ribeiro, A. A.; Sales, F. A. L.; Monteiro, R. N. F. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The coriander is widely used in Brazilian cuisine, especially in the Northeast. As the availability of good quality water for irrigation is increasingly scarce, the use of saline water becomes an alternative when working with tolerant species and through proper management practices. Therefore, this study aimed to evaluate the germination and early growth of irrigated coriander in different levels of salinity of the water. The work was carried out in two steps, both in IFCE dependencies, Campus Sobral. The first stage consisted of tests aimed to obtain electrical conductivity curves as a function of NaCl concentration. In the second stage water slides were applied with different electrical conductivities in coriander culture. The variables analyzed were: first count, germination speed index, germination percentage, average time of germination, seedling height, number of true leaves, dry matter of shoot and root. The results showed no significant difference between treatments for the analyzed variables. The culture was tolerant to salinity of the water until the concentration of 5.5 dS m-1 in seed germination and early development.